MARA: maniobra de aproximación a la realidad para el antepié - Gómez Martín, Beatriz; Becerro de Bengoa Vallejo, Ricardo; Losa Iglesias, Marta Elena; Sánchez Gómez, Rubén (Revista Internacional de Ciencias Podológicas, 2007)
It is very well well-known by all clinicians that the Root maneuver to interpret the hypothetical position who fore foot adopts during the march. In our eagerness to find new tests that approach us more the understanding of real behavior of foot in dynamics, that finally it´s the way to understand the successes and the failures when we prescribe orthopaedic treatments, we have devised a test that try to come near to the dynamic of the forefoot during gait, called MARA. - MANEUVER TO APPROACH TO FOREFOOT REALITY. The flexors and extersors muscles action is observed due to it´s very important the position that adopts the foot in dynamics during the balance phase and the beginning of heel strike.